Breakthroughs : Avant-Garde Artists in Europe and America, 1950-1990. - Argan, Giulio Carlo; Arthur, Paul; Ashton, Dore; Baker, Kenneth; Banes, Sally; Bender, Gretchen; Bourdon, David; Bremner, Ann; Burden, Chris; Celant, Germano; Close, Roy, M.; Cochran, Malcolm; et al. (Columbus (Ohio - U.S.A.) : Wexner Center for the Arts, The Ohio State University Columbus, 1991)
Nevelson, Louise ; Manzoni, Piero ; Tingueley, Jean ; Fontana, Lucio ; Warhol, Andy ; Oldenburg, Claes ; de Kooning, Willem ; Rauschenberg, Robert ; Johns, Jasper ; Burri, Alberto ; Klein, Yves ; de Saint Phalle, Niki ; Lichtenstein, Roy ; Stella, Frank ; Hesse, Eva ; Cage, John ; Cornell, Joseph ; Jacob, Ken ; Benglis, Lynda ; Paik, Nam June ; Baldessari, John ; Bourgeois, Louise ; Beuys, Joseph ; Judd, Donald ; Martin, Agnes ; Riverhead (New York) ; LeWitt, Sol ; Kosuth, Joseph ; Smithson, Robert ; Kounellis, Jannis ; Piper, Adrian ; Polke, Sigmar ; Immendorff, Jörg ; Kiefer, Anselm ; Gilbert & George ; Rothenberg, Susan ; Kaprow, Allan ; Childs, Lucinda ; Rainer, Yvonne ; Monk, Meredith ; Brown, Trisha ; Fenley, Molissa ; Anderson, Laurie ; Schneemann, Carolee ; Rappaport, Mark ; Burnett, Charles ; Cheang, Shu Lee ; Kalin, Tom ; Minh-ha, Trinh T. ; Kawamata, Tadashi ; Hamilton, Ann ; Abakanowicz, Magdalena ; Bender, Gretchen ; Burden, Chris ; Cochran, Malcolm ; Fortuyn/O'Brien ; Kruger, Barbara ; Marclay, Christian ; MICA-TV (Carole Ann Klonarides & Michael Owen) ; Zorio, Gilberto ; Gray, Spalding ; Jones, Bill T.
Engels
boek
Keywords: Amerika; Europa; Italië